Exosomes derived from liver failure patients’ plasma stimulated mesenchymal stem cells alleviate acute liver failure - Zhuoran Wang; Jun Ling; Shaoli You; Bing Zhu (Stem Cell Research & Therapy)
Abstract Background Exosomes derived from pre-stimulated mesenchymal stem cells (MSCs) have improved therapeutic effects in disease-associated microenvironments. In this study, we investigated the therapeutic potential of exosomes from MSCs stimulated with plasma from patients with liver failure (LF-Exos). Methods Untreated exosomes (NC-Exos) and LF-Exos were extracted and characterized by nanoparticle tracking analysis (NTA), transmission electron microscopy (TEM), western blotting, and miRNA sequencing. We then examined the protective effects of LF-Exos on hepatocytes acutely injured by D-galactosamine (D-GalN)/lipopolysaccharide (LPS) co-treatment and on a mouse model of acute liver failure (ALF). Apoptosis was assessed using the CCK-8 assay and flow cytometry. Liver tissue damage was examined by hematoxylin and eosin staining and immunohistochemistry. The levels of signaling pathway proteins were determined by western blotting. Results Stimulation with plasma from patients with liver failure significantly altered the morphology of MSCs and reduced their proliferative activity. Gene chip analysis identified 31 differentially expressed miRNAs, and further analysis showed that these differentially expressed miRNAs may affect the PI3K-AKT signaling pathway. Compared to NC-Exos, LF-Exos induced AKT phosphorylation in hepatocytes and liver tissues, inhibited D-GalN/LPS-induced apoptosis in hepatocytes, and reduced pathological liver injury in the mouse model of ALF. Conclusion The biological effects of Exos were improved after stimulation with plasma from patients with liver failure. LF-Exos may inhibit the activity of the NLRP3 inflammasome and activate the PI3K-AKT signaling pathway to exert protective effects on acutely injured hepatocytes and a mouse model of ALF.